2015
DOI: 10.1080/09602011.2015.1051056
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury caregivers: A qualitative analysis of spouse and parent perspectives on quality of life

Abstract: The objective of this qualitative study was to examine how family caregivers of individuals with traumatic brain injury (TBI) describe their quality of life in the context of their caregiving role. Fifty-two caregivers of adults with moderate or severe TBI (n = 31 parents, n= 21 partners/spouses (77% female, Mean age = 57.96 year, range = 34-78 years) were recruited from three data collection sites to participate in focus groups. Thematic content analysis was used to identify two main meta-themes: Caregiver Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 41 publications
4
76
0
8
Order By: Relevance
“…First, the majority of caregivers were spouses. We have previously discovered differences between parent and spouse caregivers of civilians with TBI 41 and differences by relationship type should be explored in caregivers of military TBI. We also did not examine the impact that length of time providing care had on the caregiver role.…”
Section: Discussionmentioning
confidence: 99%
“…First, the majority of caregivers were spouses. We have previously discovered differences between parent and spouse caregivers of civilians with TBI 41 and differences by relationship type should be explored in caregivers of military TBI. We also did not examine the impact that length of time providing care had on the caregiver role.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of caregivers lack the time or energy to care for themselves and often experience declining health after assuming that responsibility [6,16]. Among parents caring for children with a burn injury, perceived lack of support was significantly associated with symptoms of general anxiety and depression [15].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of slight recovery of oral intake were organized based on the following themes: reconstructing and/or strengthening a sense of family belonging, combining oral intake and other rehabilitation, reducing the burden of providing care, and relieving social isolation. These themes, especially “relieving social isolation,” may reflect that “food provides more than nutrition.” Several studies indicated that caregivers of community‐dwelling patients with stroke or TBI feel emotionally overwhelmed and that their family dynamics shifted dramatically . Our findings highlighted that even a slight recovery of oral intake in patients living with a PEG tube for EN led to positive impacts on emotionally overwhelmed caregivers.…”
Section: Discussionmentioning
confidence: 68%
“…29 Several studies indicated that caregivers of community-dwelling patients with stroke or TBI feel emotionally overwhelmed and that their family dynamics shifted dramatically. [30][31][32] Our findings highlighted that even a slight recovery of oral intake in patients living with a PEG tube for EN led to positive impacts on emotionally overwhelmed caregivers. Moreover, we would like to propose that the evaluation criteria for swallowing rehabilitation of patients requiring HEN need to include the various impacts on caregivers because eating behaviors impact the family dynamics and caregivers' own life.…”
Section: Discussionmentioning
confidence: 92%